Diagnóstico e solução para patologias causadas por sistemas de climatização na UTFPR campus Campo Mourão - Costa, Vitor Fulanetti (2022)
The term pathology for civil engineering is the study of problems that impair the durability and well-being of a building, such as cracks, fissures, mold, among others. The present work aims to identify and propose solutions to the problems encountered at the Federal Technological University of Paraná Campus Campo Mourão, related to poor installation of air conditioners. To identify the pathologies, a visual and photographic survey was carried out. It is worth mentioning that the most recurrent problems were the change in the facade of the blocks and the lack of the correct completion of the installation of the drains, these causing infiltrations, mold and mildew, in some cases. In this way, it can be concluded that it is necessary to carry out maintenance for the drains and to use the proposed solution for new building projects for the university.